Analysis of Relation Between Risk-Based Work Breakdown Structure (WBS) on Integrated Design and Construction Works of Design and Build Contract on Mechanical and Electrical Works of High Rise Building for Improving Safety Performance - Feronica Damanik, Mariana; Latief, Yusuf; Nugroho, Danang Budi (Publisher Cv. Inara, 2023)
The construction industry has had the highest accident rate worldwide for decades. Identifying risks as early as feasible during the pre-construction or design phase is essential to preventing construction accidents. To generate a structured list of risks, a Work Breakdown Structure (WBS) is used to identify risks. Although numerous studies have proposed using Work Breakdown Structure (WBS) to identify risks, no one has analyzed the relationship between Work Breakdown Structure (WBS) and risk to reduce construction accidents. Consequently, this study aimed to investigate the impact of Work Breakdown Structure (WBS) risk during the design and construction phases on construction safety performance. The analysis of relationships will be conducted using statistical methodologies. The study's findings will demonstrate that Work Breakdown Structure (WBS) risk affects construction safety performance.